PENGARUH JUMLAH DAN SUDUT PEMASANGAN SUDU TERHADAP DAYA TURBIN SAVONIUS - Purwoko, Purwoko (Universitas Lambung Mangkurat, 2020)
The problem in Energy conservation is finding new opportunities for high-efficiency energy generation including wind power generating machines. Aims of this study to determine the effects of blade number and curv angle of blade mounting on the output power of a Savonius type wind turbine. This low speed wind turbine is intended to get energy at the top of a multi-storey building in an urban area. Tests were carried out on a laboratory scale, using savonius wind turbines with 400 mm diameter and 500 mm height. The driving wind speed of the turbine is set between 1.5 to 8.5 m / s. While the number of blades used is 2 types, namely rotor with three blades and rotor with 4 blades, each of which is tested on 3 different types of curv angle blade. The investigation results are expected to show that the wind tubing from each experiment will give different characteristics. This investigation results that there was increasing in efficiency in the savonius turbine with blades. The highest rotation and power occur when the turbine uses 2 blades and -50 curv angle of blade mounting